A Literature Review on Photodynamic Therapy Efficacy in Dental Managements - Mohammad Mostafa Aghamohseni; Seyed Ali Jafarian Mohammadi (Isfahan University of Medical Sciences, 2023)
The use of photodynamic therapy is a relativelynew approach in medical science with an old background. In this method, it is possible to use light to inactivate and destroy cells and microorganisms. In dental treatments, it can be effective in many aspects of treatment, such as the treatment of gum diseases, oral and premalignant lesions, and root canal treatment. Initially introduced as an anti-infective treatment, photodynamic therapy has become a promising treatment method due to various advances in this field.Description:According to the variousfindings of this study, photodynamic therapy can be useful as an adjuvant treatment of gum diseases and root canal treatment as as it is a minimally invasive process and can improve the treatment outcomes. Additionally, it can be used in the treatment of premalignant and superficial lesions in the head and neck region, as well as for early diagnosis of premalignant lesions with the potential to become malignant.Conclusion:According to the recent advances regarding the use of photodynamic therapy in dental managements, today this method can be used as an adjuvant treatment in many dental procedures. In addition, further studies are needed to show the use of photodynamic therapy as an independent treatment in dental managements